Rhizopus homothallicus, an emerging pathogen causing cavitary lung lesions. Issue 4 (21st April 2023) - Taneja, Juhi; Chatterjee, Kuhu; Sachdeva, Ruchi Arora; Abbas, S. Zafar; Sen, M.K.
Abstract : Introduction. Rhizopus homothallicus is an emerging pathogen that causes pulmonary mucormycosis. Case Presentation. We report a case of pneumonia caused by R. homothallicus in a 54-year-old type 2 diabetic patient. The organism was isolated from bronchoalveolar lavage fluid and preliminarily identified by fungal morphology and finally by sequencing of the internal transcribed spacer region. Conclusion. Mucormycosis may be associated with cavitary lung lesions against a backdrop of poorly controlled diabetes or other immunosuppressed states. Pulmonary mucormycosis may have variable clinical and radiological presentations. Therefore, strong clinical suspicion and prompt management can address the high fatality associated with the disease.